11 nm hard X-ray focus from a large-aperture multilayer Laue lens - Huang, Xiaojing (Nature Publishing Group, 2013)
The focusing performance of a multilayer Laue lens (MLL) with 43.4 μm aperture, 4 nm finest zone width and 4.2 mm focal length at 12 keV was characterized with X-rays using ptychography method. The reconstructed probe shows a full-width-at-half-maximum (FWHM) peak size of 11.2 nm. The obtained X-ray wavefront shows excellent agreement with the dynamical calculations, exhibiting aberrations less than 0.3 wave period, which ensures the MLL capable of producing a diffraction-limited focus while offering a sufficient working distance. This achievement opens up opportunities of incorporating a variety of in-situ experiments into ultra high-resolution X-ray microscopy studies.